Cover Image. Issue 9 (29th August 2018) - Xiao, Yichen; Xu, Wenna; Su, Wenru
Abstract : The cover image, by Yichen Xiao et al., is based on the Review NLRP3 inflammasome: A likely target for the treatment of allergic diseases, https://doi.org/10.1111/cea.13190 .